Managerial Challenges Under FinTech: Evidence From Zimbabwean Commercial Banks - Mufaro Dzingirai (IGI Global, 2022)
FinTech has become an increasingly important phenomenon around the world in recent times. This is substantiated by a growing interest from researchers, academicians, and policymakers. While the adoption of FinTech appears to be widely regarded as a strategic priority for financial institutions worldwide, the empirical evidence on the managerial challenges under FinTech is very scant, especially from the perspective of developing countries. With this in mind, this chapter aims at providing empirical evidence on the managerial challenges emanating from FinTech within the context of Zimbabwean commercial banks. The study establishes seven challenges, namely, customer retention, regulatory compliance, technology risk, increased competition, cyber-attacks, the inadequacy of IT employees, and system downtimes. The recommendations to deal with these challenges are proffered and the suggestions for further study are captured.